2018
DOI: 10.1007/s00170-018-2520-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tool deflection during milling of thread in Cr-Co dental implant

Abstract: Milling is a good option for manufacturing internal threads in hard-to-cut dental components due to lower cutting forces. In the case of a very small drilled diameter, the tool cannot be large enough to reduce tool deflection nor sufficiently small to avoid the influence of the tool penetration. As a consequence, both situations need to be considered and no other research study dealt with this aspect for the modeling of thread milling forces. This article deals with the analysis of forces, deflection, and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, some studies have focused on the effects of cutting force and cutting torque dynamics during thread milling. For example, Araujo and Fromentin [5] studied the relationship between the cutting forces and tool deflection in a typical internal thread machining and proposed a tool trajectory planning method for the hard-to-cut materials by considering the tool deflection characteristics. Sharma et al [6] studied the influence of tool geometry on the cutting forces and concluded that the cutting forces can be minimized by applying a proper penetration strategy for the cutting tool.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, some studies have focused on the effects of cutting force and cutting torque dynamics during thread milling. For example, Araujo and Fromentin [5] studied the relationship between the cutting forces and tool deflection in a typical internal thread machining and proposed a tool trajectory planning method for the hard-to-cut materials by considering the tool deflection characteristics. Sharma et al [6] studied the influence of tool geometry on the cutting forces and concluded that the cutting forces can be minimized by applying a proper penetration strategy for the cutting tool.…”
Section: Related Workmentioning
confidence: 99%
“…Jun and Araujo 15 investigated the thread milling process by using a thrilling tool that can perform both drilling and thread milling operations. Araujo and Fromentin 16 used the thread milling process in the production of micro threaded holes (M2) for dental implants and stated that undercut material due to the tool deflection can be machined with extra pass. Khorasani et al 17 investigated the effect of cutting fluid pressure on the surface quality in the thread milling of two different workpieces and stated that the fluid pressure is an important parameter in achieving better surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…Tapping is a process widely used in the manufacturing of internal threads. Although in the past few years, other processing methods have been used to manufacture internal threads with great success, such as thread milling and turning [11][12][13][14][15][16], tapping is almost the only method to manufacture small diameter internal threads [17]. However, there are relatively few literatures on thread quality in tapping.…”
Section: Introductionmentioning
confidence: 99%